How to improve your sleep quality? Review of non-pharmacological methods - Szymczak, Urszula; Lachór, Wojciech Wiesław; Solarz, Monika Barbara; Piekarska, Julia; Solarz, Justyna Maria; Wawrzyńców, Jakub Tomasz; Cyrkler, Weronika; Robak, Jakub; Telega, Stanisław; Bollin, Paweł (Quality in Sport, 2025)
Sleep disorders are a common problem for a large part of society, affecting people of all ages. Sleep is an essential element of the circadian rhythm, and its deprivation has an impact on many aspects of health. Long-term deprivation translates into reduced efficiency, concentration, increased anxiety, lowers the quality of life, and worsens academic and professional outcomes. The objective of this article is to expand knowledge on non-pharmacological methods of improving sleep quality. Article was based on 24 selected articles, related to the topic of sleep and non-pharmacological methods of improving its quality, searched through the PubMed database. Selected methods such as: Aromatherapy, Physical exercises, Mindfulness Meditation, Music and Relaxing sounds, and Cognitive-Behavioral Therapy (CBT) are known for treating/relieving sleep problems. They show a varied effect on sleep parameters such as the number of awakenings, total sleep duration, subjective sleep quality, and ease of falling asleep. The research found that non-pharmacological methods of improving sleep quality present varying effectiveness depending on the parameter studied. They are an effective element of relieving these disorders, but in the case of more complex or severe cases they may not be sufficient. More studies conducted on different groups of people and their comparison with pharmacological methods are needed to determine their exact effectiveness.